Secondary Atomization of a Biodiesel Micro-Emulsion Fuel Droplet Colliding with a Heated Wall; Applied Sciences; Vol. 10, iss. 2 - Ashikhmin A. E. Alexander Evgenjevich; Khomutov N. A. Nikita Andreevich; Piskunov M. V. Maksim Vladimirovich; Yanovsky V. A. Vyacheslav Aleksadrovich (2020, 2020)
Title screen